Neuroendoscopic hematoma evacuation vs. craniotomy in hypertensive intracerebral hemorrhage: a retrospective comparative study on surgical efficiency and long-term functional outcomes - Ye, Xinyun; Huang, Guanlin; Hu, Jing; Lai, Wentao (Frontiers in Surgery, 2025)
ObjectiveTo investigate the impact of neuroendoscopic surgery on surgical efficiency and long-term functional outcomes in patients with hypertensive intracerebral hemorrhage (HICH).MethodsThis retrospective comparative study was conducted on a cohort of 60 patients diagnosed with HICH who were admitted to Ganzhou People's Hospital between January 2020 and December 2022. The patients were divided into two groups based on the surgical technique employed: neuroendoscopic hematoma evacuation (NEHE, n = 30) and traditional craniotomy hematoma evacuation (CHE, n = 30). Primary outcomes measured included operative time, intraoperative blood loss, hematoma clearance rate, and long-term functional recovery assessed at the one-year follow-up using the Stroke-Specific Quality of Life Scale (SS-QOL), Modified Barthel Index (MBI), and Fugl-Meyer Assessment (FMA).ResultsThe NEHE group demonstrated statistically significant improvements in surgical efficiency and safety. Specifically, the operative time was reduced by 25% (93.75 ± 10.56 min vs. 124.66 ± 21.71 min, p < 0.001), and intraoperative blood loss decreased by 44% (30.32 ± 5.63 mL vs. 53.75 ± 10.56 mL, p < 0.001), indicating markedly lower surgical trauma compared to CHE. Notably, the hematoma clearance rate in the NEHE group (84.66 ± 7.33%) surpassed that of CHE (80.21 ± 8.54%, p = 0.03), which may correlate with enhanced visualization of residual clots under endoscopic guidance. At 1-year follow-up, NEHE patients exhibited superior functional recovery, with SS-QOL scores increasing by 13% (156.74 ± 26.64 vs. 138.22 ± 34.45, p = 0.03), MBI scores by 20% (59.34 ± 11.51 vs. 49.22 ± 16.71, p = 0.01), and FMA scores by 23% (35.27 ± 3.98 vs. 28.63 ± 5.72, p < 0.001). Crucially, stratified analysis revealed maximal functional benefits in basal ganglia hemorrhages where FMA scores were 27% higher with NEHE (37.12 ± 3.15 vs. 29.23 ± 4.82, p < 0.001), contrasting with non-significant differences in lobar hemorrhages (p = 0.41).ConclusionIn summary, our findings affirm that NEHE provides superior surgical outcomes and a favorable safety profile in the management of HICH, with significant improvements noted in long-term quality of life and motor function. The results advocate for the adoption of NEHE as a primary approach for HICH cases.